Analysis of Luminex-based Algorithms to Define Unacceptable HLA Antibodies in CDC-crossmatch Negative Kidney Transplant Recipients. Issue 6 (June 2018) - Zecher, Daniel; Bach, Christian; Preiss, Adrian; Staudner, Christoph; Utpatel, Kirsten; Evert, Matthias; Jung, Bettina; Bergler, Tobias; Böger, Carsten A.; Spriewald, Bernd M.; Banas, Bernhard
Abstract : Background: HLA-specific antibodies detected by solid phase assays are increasingly used to define unacceptable HLA antigen mismatches (UAM) before renal transplantation. The accuracy of this approach is unclear. Methods: Day of transplant sera from 211 complement-dependent cytotoxicity crossmatch-negative patients were retrospectively analyzed for donor-specific anti-HLA antibodies (DSA) using Luminex technology. HLA were defined as UAM if DSA had mean fluorescence intensity above (I) 3000 (patients retransplanted and those with DSA against HLA class I and II) or 5000 (all other patients), (II) 5000 for HLA-A, -B, and -DR and 10 000 for HLA DQ or (III) 10 000 (all HLA). We then studied the accuracy of these algorithms to identify patients with antibody-mediated rejection (AMR) and graft loss. UAM were also determined in 256 transplant candidates and vPRA levels calculated. Results: At transplantation, 67 of 211 patients had DSA. Of these, 31 (algorithm I), 24 (II) and 17 (III) had UAM. Nine (I and II) and 8 (III) of 11 early AMR episodes and 7 (I), 6 (II) and 5 (III) of 9 graft losses occurred in UAM-positive patients during 4.9 years of follow-up. Algorithms I and II identified patients with persistently lower glomerular filtration rate even in the absence of overt AMR. Of the waiting list patients, 22–33% had UAM with median virtual panel reactive antibody of 69.2% to 79.1%. Conclusions: Algorithms I and II had comparable efficacy but were superior to Algorithm III in identifying at-risk patients at an acceptable false-positive rate. However, Luminex-defined UAM significantly restrict the donor pool of affected patients, which might prolong waiting time. Abstract : In a retrospective series of 211 kidney transplant recipients, the authors suggest 3 algorithms based on DSA-MFI in order to more accurately define unacceptable mismatches. Supplemental digital content is available in the text.